Prognostic Value of Circulating MG53 Levels in Acute Myocardial Infarction - Xie, Hongyang; Yan, Zijun; Feng, Shuo; Zhu, Tianqi; Zhu, Zhengbin; Ni, Jingwei; Ni, Jun; Du, Run; Zhu, Jinzhou; Ding, Fenghua; Liu, Shengjun; Han, Hui; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: Mitsugumin 53 (MG53), a muscle-specific protein belonging to the TRIM family, has been demonstrated to protect the heart against oxidative injury. Although previous studies indicated that ischemic hearts released MG53 into circulation in mice, its effects in humans remains unknown. We aimed to evaluate the prognostic value of MG53 in patients with ST-segment elevation myocardial infarction (STEMI). Methods: Serum levels of MG53 were measured in 300 patients with STEMI, all patients were followed for 3 years. The primary endpoint was major adverse cardiovascular events (MACE), defined as a composite of cardiovascular (CV) death, heart failure causing-rehospitalization, recurrent myocardial infarction (MI), and stroke. Results: Patients with a higher concentration of serum MG53 tended to be older, with a history of diabetes. MG53 levels were also highly associated with indicators reflecting heart function, such as left ventricular ejection fraction (LVEF), N terminal pro B type natriuretic peptide (NT-pro-BNP), and cardiac troponin I (cTnI) at baseline. Kaplan-Meier survival curves demonstrated that patients with MG53 levels above the cutoff value were more likely to have MACEs. Moreover, it was found to be a significant predictor of CV death (HR: 6.12; 95% CI: 2.10 to 17.86; p = 0.001). Furthermore, the C-statistic and Integrated Discrimination Improvement (IDI) values for MACEs were improved with MG53 as an independent risk factor or when combined with cTnI. Conclusions: MG53 is a valuable prognostic marker of MACE in patients with AMI, independent of established conventional risk factors, highlighting the significance of MG53 in risk stratification post-MI.